Persepsi Mahasiswa Perempuan Terhadap Keberadaan Akun Instagram @umcantik_id - Nailah Zulfa Khairunnisa; Naila Naswa Salsabila; Nahlatus Salsabilah (Pusat Studi Wanita dan Keluarga UGM, 2026)
Social media has become a public space that highlights the importance of physical appearance and influences how individuals judge their appearance. One phenomenon that has emerged in Indonesia is the existence of beautiful campus accounts, such as @unpad.geulis, @ugmcantik, @ubcantikid, and @unejcantik. Women are often objectified on social media, so we wanted to study the Instagram account @umcantik_id to explore female students' perceptions of the existence of the “umcantik_id” account at Malang State University. The method used is qualitative research with an exploratory approach design that aims to find out “what happened,” “seek new insights,” and